1997
DOI: 10.1111/j.1559-1816.1997.tb00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perceived Social Support on Depression in Chinese Adolescents: A Prospective Study Examining the Buffering Model

Abstract: In response to the dearth of attempts to examine functions of perceived social support on depression in Chinese adolescents, a prospective study was conducted to examine the relationship among stressful life events, perceived social support, and depression. The present results provided support for the buffering model, indicating that the function of perceived social support in mitigating subsequent depression was prominent only under high stress levels. These results were discussed in terms of the socialized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 44 publications
6
38
1
1
Order By: Relevance
“…While the results regarding perceived support from parents, classmates, and the school parallel those of previous studies (Cheng, 1997;Forman, 1988;Garnefski & Diekstra, 1996;Kashani et al, 1994;Licitra-Kleckler & Waas, 1993;Wenz-Gross et al, 1997), the lack of significant findings regarding teacher support contradicts prior research (Demaray & Malecki, 2002b, Malecki & Demaray, 2003. One possible explanation for this lack of significant findings may be that participants in this study experienced different sets of teachers across the three time points.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…While the results regarding perceived support from parents, classmates, and the school parallel those of previous studies (Cheng, 1997;Forman, 1988;Garnefski & Diekstra, 1996;Kashani et al, 1994;Licitra-Kleckler & Waas, 1993;Wenz-Gross et al, 1997), the lack of significant findings regarding teacher support contradicts prior research (Demaray & Malecki, 2002b, Malecki & Demaray, 2003. One possible explanation for this lack of significant findings may be that participants in this study experienced different sets of teachers across the three time points.…”
Section: Discussioncontrasting
confidence: 78%
“…For example, adjustment and behavioral problems (Dunn, Putallaz, Sheppard, & Lindstrom, 1987;Kashani, Canfield, Borduin, Soltys, & Reid, 1994), delinquency (Licitra-Kleckler & Waas, 1993), withdrawn behavior and hopelessness (Kashani et al, 1994), emotional problems (Garnefski & Diekstra, 1996), depression (Cheng, 1997;Licitra-Kleckler & Waas, 1993) and lower self-concept (Forman, 1988;Wenz-Gross, Siperstein, Untch, & Widaman, 1997) have been shown to be related to low levels of family and peer support. Domitrovich and Bierman (2001) found that warm supportive parental practices were negatively related to different aggression and positively related to prosocial behaviors.…”
Section: Relationship Between Social Support and Adjustment: Cross-sementioning
confidence: 97%
See 1 more Smart Citation
“…Thus low peer and family support are associated with negative indicators. Specifically, low levels of both peer and family support are associated with adjustment and behavioral problems (Dunn, Putallaz, Sheppard, & Lindstrom, 1987;East, Hess, & Lerner, 1987;Kashani, Canfield, Borduin, Soltys, & Reid, 1994), delinquency (Licitra-Kleckler & Waas, 1993), withdrawn behavior and hopelessness (Kashani et al, 1994), emotional problems (Garnefski & Diekstra, 1996), depression (Cheng, 1997;Licitra-Kleckler & Waas, 1993), and lower self-concept (Forman, 1988;Wenz-Gross, Siperstein, Untch, & Widaman, 1997). A higher level of family support is more often associated with better school adjustment and higher academic self-concept (Dunn et al, 1987;.…”
Section: Social Support and (Mal)adjustmentmentioning
confidence: 95%
“…Efectivamente, la investigación también ha mostrado la importancia de la integración y el apoyo social para el ajuste psicosocial de los inmigrantes (Cheng, 1997;Díez-Nicolás, 2005;Leslie, 1992;Martínez, García y Maya, 1999;Mui, 2001;Vega, Kolody, Valle y Weir, 1991). Diversos estudios desarrollados en nuestro país con población inmigrante han constatado la importancia que tiene el apoyo social, especialmente en sus aspectos funcionales, en su bienestar y ajuste García-Ramírez, Martí-nez, Albar y Santolaya, 2002;Hernández, Alonso y Pozo, 2006;Hernández, Pozo, Alonso y Martos, 2005;Martínez, García y Maya, 2001.…”
Section: Integración Social Y Bienestarunclassified